A sensitive quantitative assay for the determination of propafenone and two metabolites, 5‐hydroxypropafenone and N‐depropylpropafenone, in human K2EDTA plasma using LC–MS/MS with ESI operated in positive mode. (7th May 2017) - Patel, Harilal; Ghoghari, Ashok; Bhatt, Chandrakant; Shah, Shaival; Jha, Anilkumar; Desai, Nirmal; Srinivas, Nuggehally R.
Abstract: Propafenone is a potent antiarrhythmic agent; clinically propafenone has been used for a number of cardiac arrhythmias because it possesses multiple modes of action, via beta adrenergic receptor blockade and calcium antagonistic activity. Propafenone (PPF) exhibits extensive saturable presystemic biotransformation (first‐pass effect) resulting in two active metabolites: 5‐hydroxypropafenone (5‐OH PPF) formed by CYP2D6 and N‐ depropylpropafenone (NDP) formed by both CYP3A4 and CYP1A2 enzymes. A specific and sensitive LC–MS/MS method was developed and validated for quantitation of PPF, 5‐OH PPF and NDP using turboion spray in a positive ion mode. A solid‐phase extraction was employed for the extraction from human plasma. Chromatographic separation of analytes was achieved using an ACE‐5 C8 (50 × 4.6 mm) column with a gradient mobile phase comprising ammonium acetate containing 0.01% TFA in purified water and acetonitrile. The retention times achieved were 1.36, 1.23, 1.24 min and 1.34 min for PPF, 5‐OH PPF, NDP and IS (carbamazepine), respectively. Quantitation was performed by monitoring multiple reaction monitoring transition pairs of m / z 342.30 to m / z 116.20, m / z 358.30 to m / z 116.20, m / z 300.30 to m / z 74.20 and m / z 237.20 to m / z 194.10, respectively. The developed method was validated for various parameters. The calibration curves of PPF and 5‐OH PPF showed linearity from 1 to 500 ng/mL, with a lower limit of quantitation of 1.0 ng/mL and for NDP linearity from 0.1 to 25 ng/mL with a lower limit of quantitation of 0.1 ng/mL. The bias and precision for intra‐ and‐inter batch assays were <10 and 5%, respectively. The developed assay was used to evaluate pharmacokinetic properties of propafenone and its major metabolites in healthy human subjects.